Reviews of recent publications (Studies in 20th & 21st Century Literature, 2006)
Julian W. Connolly, ed. The Cambridge Companion to Nabokov. Thomas Seifrid Simon Franklin and Emma Widdis, eds. National Identity in Russian Culture: An Introduction. Keith Livers Sander L. Gilman. Franz Kafka. Esther K. Bauer Jill Robbins, ed. P/herversions: Critical Studies of Ana Rossetti. Roberta Johnson Jennifer Warburton. John Fowles: A Life in Two Worlds. John Fowles. The Journals, Vol. I. Ed. Charles Drazin Gerd Bayer
Keywords: Julian W. Connolly; The Cambridge Companion to Nabokov; Thomas Seifrid; Simon Franklin; Emma Widdis; National Identity in Russian Culture: An Introduction; Keith Livers; Sander L. Gilman; Franz Kafka; Esther K. Bauer; Jill Robbins; P/herversions: Critical Studies of Ana Rossetti; Roberta Johnson; Jennifer Warburton; John Fowles: A Life in Two Worlds; John Fowles; The Journals Vol. I; Charles Drazin Gerd Bayer